231Pa/230Th: a proxy for upwelling off the coast of West Africa - Christl, Marcus; Lippold, Jörg; Hofmann, Alexander; Wacker, Lukas; Lahaye, Yann; Synal, Hans-Arno (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2010)
231Pa has widespread applications in the earth sciences including uranium series disequilibrium dating of carbonates and the reconstruction of ocean circulation or bio-productivity on glacial/interglacial timescales. Here we present the first 231Pa profile from a marine sediment core (GeoB3722) located in the large upwelling area off West Africa (Northern Cape Basin) measured with Accelerator Mass Spectrometry (AMS). Together with the Th and U-data (obtained with ICP-MS) 231Pa/230Th ratios were calculated covering the past 30,000yr. Our results indicate that site GeoB3722 was located in the wind driven upwelling area during glacial times while it abruptly turned into an open ocean area at about 14,000yr BP. A spatial shift of the large wind driven upwelling area off West Africa is consistent with the idea that atmospheric circulation patterns as well as ocean circulation dramatically changed at the last glacial interglacial transition.